Conflict Management In Inter-racial Relationships - Andika Sakti D; Nuriyatul Lailiyah, S.Sos, M.I.Kom (Interaksi Online, 2016)
Based on the principle of conformity, a person tends to prefer a partner who has in common with him. But as the times goes by along with the era which is increasingly open, we have encountered inter-racial relationships, including in Indonesia. When couples come from different cultural backgrounds, the values, rules, standpoints, habits, and methods that used in relationship must also be different. The characteristics differences are tend to be the cause of conflict on inter-racial relationships. Especially for those who have contrast cultures such as Javanese-European couples. The method that used in this reserach is qualitative research with phenomenological approach. The purpose of this research is to understand style of conflict management on inter-racial relationships. The theories that used in this research are Triangular Theory of Love, High and Low Context Cultures, and Conflict Management. The results of this reserach indicates: (1) Both couples are belong to fatuos love. (2) The couples who come from different countries have different cultural characteristics. (3) Generally the conflict that occurs on inter-racial relationships is about misunderstanding which triggered by cultural characteristics differences, stereotypes, prejudice and ethnocentrism. (4) The couples using model, form and combination of a specific patterns to resolve the conflict. (5) There is a difference of opinion regarding to conflict resolution that using the assistance of third party. This research concluded that the couples using different model, form and combination of a specific patterns to resolve the conflict. Usually the Javanese women use avoidance at the beginning of the conflict, while the men who come from Europe use competition and accommodation to resolve the conflict. We can suggest the couples to have disclosure so the conflict can be minimized and solved easier. They can ask a trusted third party to help searching the solution if it needed.